Examining Student Resilience by Observing the Effect of Social Support and Optimism - Widuri, Erlina Estiyanti; Mujidin, Mujidin; Rustam, Husnul Khotimah; Rohmah, Miftakhur (Jurnal Kajian Bimbingan dan Konseling, 2023)
There are many negative situations that make students depressed and very stressed with their academics. Students who lack endurance need conducive conditions through social support and strong optimism. This study aimed to test the effect of social support and optimism on the resilience of students working on their thesis. The subjects involved were 79 active students of the faculty of psychology. This study was conducted with quantitative methods using three scales: resilience, social support, and optimism. Sampling was performed using the purposive sampling technique, while the analysis employed the multiple linear regression technique. The results of the major hypothesis analysis show a very significant relationship between social support and student optimism and the resilience of students working on their thesis. The findings of this study can be a significant discussion topic for researchers or other education practitioners to prioritize establishing student resilience in writing final projects and encourage further research related to predominant factors that influence the attitudes of final-year students.